Pencegahan Hoax di Media Sosial : Studi Kriminologi dan Kesadaran Hukum Masyarakat Digital - Syah Awaluddin; Moh Yamin Rumra; Moh Zidan Rumra (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The phenomenon of hoaxes in the digital era has become a serious threat to social stability, democracy, and national security. Although the government has implemented various regulations, such as the Electronic Information and Transactions Law (UU ITE), the spread of hoaxes is still difficult to control. This article analyzes the development of legal awareness in overcoming hoaxes in Indonesia from a criminological perspective. With a literature study approach, this study highlights the weak legal awareness of the community as the main factor in the spread of hoaxes. Empirical studies show that political hoaxes dominate, with 55.5% of the total hoaxes identified in 2023, while 65% of hoaxes spread through closed WhatsApp groups. Criminological analysis uses several theories, such as the Theory of Crime Routines, Anomie Theory, and Differential Association Theory, which explain how weak social control and low legal culture make it easier for individuals to be involved in the spread of hoaxes. The results of this study recommend strategies to increase legal awareness through the integration of digital literacy in education, collaboration between the government and digital platforms, and strengthening policy-based regulations such as the NetzDG Law in Germany. With a systematic and data-based approach, it is hoped that public legal awareness will increase, so that it can reduce the spread of hoaxes and create a healthier and more responsible digital environment.